Visual research methods in architecture - Troiani, Igea; Ewing, Suzanne (Intellect Books, 2020)
This book offers a distinctive approach to the use of visual methodologies for qualitative architectural research. It presents a diverse selection of ways for the architect or architectural researcher to use their gaze as part of their research practice for the purpose of visual literacy. Its contributors explore and use, "critical visualizations," which employ observation and socio-cultural critique through visual creations--texts, drawings, diagrams, paintings, visual texts, photography, film, and their hybrid forms--to research architecture, landscape design, and interior architecture. The visual methods intersect with those used in ethnography, anthropology, visual culture, and media studies. In presenting a range of interdisciplinary approaches, 'Visual Research Methods in Architecture' opens up territory for new forms of visual architectural scholarship.